Cytotoxic effects of zinc oxide nanoparticles on Chlorella Vulgaris - Djearamane, S.; Wong, L. S.; Lim, Y. M.; Lee, P. F. (EM International, 2019)
Nanoparticles such as zinc oxide nanoparticles (ZnO NPs) have a wide range of applications in industrial and personal care products, but, at the same time, the presence of nanoparticles causes negative impact to aquatic ecosystem and the organisms within. In this study, the cytotoxic effect of ZnO NPs on fresh water microalga Chlorella vulgaris is reported. C. vulgaris cells were treated with 10, 50, 100, 150 and 200 mg/L of ZnO NPs for 72 h. Cytotoxicity effects of ZnO NPs were assessed by measuring the fluorescence emission of chlorophyll using fluorescent spectrophotometer, algal biomass by spectrophotometer and cell viability through counting viable cells at 24, 48 and 72 h. Exposure to ZnO NPs caused a decrease in chlorophyll content, cell viability and algal biomass. The cytotoxic effects increased as the concentration and exposure duration of ZnO NPs increased. Toxicity of ZnO NPs was indicated by reduction in the chlorophyll content, cell viability and biomass. This study showed the potential of C. vulgaris to be a bioindicator for ZnO NPs' toxicity in aquatic environment.